« Vous êtes dans un lieu hors du monde... » : la musique dans les centres de détention de la « guerre contre la terreur » - Suzanne G. Cusick (Transposition)
Based on first-person accounts of interrogators and former detainees as well as unclassified military documents, this article outlines the variety of ways that “loud music” has been used in the detention camps of the United States‘ “global war on terror.” A survey of practices at Bagram Air Force Base, Afghanistan; Camp Nama (Baghdad), Iraq; Forward Operating Base Tiger (Al-Qaim), Iraq; Mosul Air Force Base, Iraq; Guantánamo, Cuba; Camp Cropper (Baghdad), Iraq; and at the “dark prisons” from 2002 to 2006 reveals that the use of “loud music” was a standard, openly acknowledged component of “harsh interrogation.” Such music was understood to be one medium of the approach known as “futility” in both the 1992 and the 2006 editions of the US Army’s field manual for interrogation. The purpose of such “futility” techniques as “loud music” and “gender coercion” is to persuade a detainee that resistance to interrogation is futile, yet the military establishment itself teaches techniques by which “the music program” can be resisted. The article concludes with the first-person account of a young US citizen, working in Baghdad as a contractor, who endured military detention and “the music program” for ninety-seven days in mid-2006—a man who knew how to resist.